2016
DOI: 10.2174/1871520616666160520112210
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Inhibition of Proteasome Activity and Tumour Growth by Murraya koenigii Leaf Extract in Breast Cancer Xenografts and by Its Active Flavonoids in Breast Cancer Cells

Abstract: Inhibition of the 26S proteasome is an attractive approach for anticancer therapy. Proteasome inhibitors are known to selectively target cancer cells and make them more sensitive to chemotherapeutic agents. Murraya koenigii is a medicinally important herb of Asian origin and a rich source of bioactive compounds such as flavonoids and alkaloids. In the present study, we investigated the proteasome inhibitory and apoptotic effect of M. koenigii leaf extract in vivo in a xenograft tumor mouse model, and also asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Quercetin, the most common flavonoid, has been shown to act against various cancers, including breast cancer [ 14 18 ]. Recent studies have reported that quercetin inhibits breast cancer by inhibiting signal transduction, inducing cancer cell apoptosis, and suppressing proliferation, invasion, and metastases of tumor cells [ 19 21 ]. However, the effect of quercetin on breast CSCs has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin, the most common flavonoid, has been shown to act against various cancers, including breast cancer [ 14 18 ]. Recent studies have reported that quercetin inhibits breast cancer by inhibiting signal transduction, inducing cancer cell apoptosis, and suppressing proliferation, invasion, and metastases of tumor cells [ 19 21 ]. However, the effect of quercetin on breast CSCs has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…They exert anticancer activities through their antioxidant, anti-inflammatory, anti-angiogenic, anti-proliferative, and apoptotic actions. 13 18 Myricetin has a quercetin backbone with an additional hydroxyl group ( Fig. 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…Girinimbine, another M. koenigii-derived carbazole alkaloid, showed growth inhibitory activity in human hepatocellular carcinoma and lung cancer cells in vitro [118]. Rutin, quercetin, kaempferol, and apigenin, present in leaf extracts of M. koenigii, showed the dose-dependent inhibition of endogenous 26S proteasome activity in MDA-MB-231 cells [52]. Therefore, M. koenigii contains remarkable anticancer compounds, especially mahanine, which has been reported to show anticancer activity targeting different signaling pathways [46].…”
Section: Anticancer Activity (In Vivo and In Vitro)mentioning
confidence: 99%